KEKERASAN VERBAL OLEH PRIA TERHADAP WANITA DALAM HUBUNGAN BERPACARAN: Studi Fenomenologi Pada Hubungan Berpacaran Remaja Jakarta - Nahda Chairunisa (2021)
The phenomenon of Verbal Abuse perpetrated against women occurs in DKI Jakarta indicate a high enough number. Data from Komnas Perempuan places DKI Jakarta ranked 2nd in terms of the high number of cases of verbal abuse. This phenomenon of violence is the background for the writer to study violence cases that occurred in the DKI Jakarta. To find out these things, the author conducted in-depth interviews with five victims of verbal abuse who live in the DKI Jakarta. The research questions posed are; (1) How do young women in Jakarta interpret verbal abuse by men in dating relationships? (2) How are the experiences of young women in Jakarta who get verbal abuse by men in dating relationships?. The concepts used are Verbal Communication, Violence, Verbal Abuse, Dating, Abusive Relationships. The findings obtained from the experiences of these victims are; Hope for a partner, silent and crying, afraid to tell stories, trauma, family parenting, alcohol consumption.